GREEN ECONOMY POLICY DYNAMICS: A LITERATURE REVIEW FOR THE FUTURE OF SUSTAINABILITY - Loso Judijanto; Caroline, Caroline (Prosiding Seminar Nasional Indonesia, 2025)
The green economy has emerged as an important paradigm in global efforts towards sustainable development. This literature review aims to explore the dynamics of green economy policies and their implications for the future of sustainability. By analysing various academic sources and policy reports, this study identifies key trends, challenges, and opportunities in the implementation of green economy policies in various contexts. The review shows that green economy policies have evolved significantly in the past decade, with a focus on reducing carbon emissions, resource efficiency, and green job creation. However, their implementation still faces various barriers, including technological gaps, funding limitations, and resistance from traditional economic sectors. The study also reveals the importance of an integrated approach that considers environmental, social, and economic aspects simultaneously